2006
DOI: 10.1093/brain/awl245
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity to GABAA-receptor-associated protein in stiff-person syndrome

Abstract: Stiff-person syndrome (SPS) is an autoimmune neurological disorder characterized by autoantibodies to glutamic acid decarboxylase (GAD), the enzyme responsible for the synthesis of inhibitory neurotransmitter GABA. To search for biomarkers that distinguish SPS from other neurological disorders (OND), we used surface enhanced laser desorption/ionization-time of flight (SELDI-TOF) mass spectrometry to obtain proteomic profile of sera from 25 GAD-positive SPS patients and 25 controls. A significant decrease was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(82 citation statements)
references
References 27 publications
1
72
1
8
Order By: Relevance
“…Applying GABARAP IgG from StiffPerson Syndrome patients decreased the surface GABA A receptors in cultured hippocampal neurons (Raju et al, 2006). Here, we provide additional evidence that GABARAP enhances the surface expression of GABA A receptors, suggesting that GABARAP facilitates the intracellular trafficking of GABA A receptors.…”
Section: Discussionmentioning
confidence: 50%
“…Applying GABARAP IgG from StiffPerson Syndrome patients decreased the surface GABA A receptors in cultured hippocampal neurons (Raju et al, 2006). Here, we provide additional evidence that GABARAP enhances the surface expression of GABA A receptors, suggesting that GABARAP facilitates the intracellular trafficking of GABA A receptors.…”
Section: Discussionmentioning
confidence: 50%
“…110 Receptors for glutamate and GABA can act as targets for autoantibodies, resulting in symptoms associated with those often seen in ASD. For example, antibodies against glutamate receptors have been implicated in childhood seizure disorders, 112 a common comorbidity of ASD, 111,112 whereas antibodies against GABA recep- tors are associated with motor disorders, 113 which are widely reported in ASD. 114 Although antibodies for either receptor family have not been detected in ASD, numerous unknown targets for autoantibodies exist, and it is possible that these could include subunits of the GABA or glutamate receptors.…”
Section: Neurotransmittersmentioning
confidence: 99%
“…Therefore, the reduced FMZ binding is best explained by reduced GABA-A receptor density on neuronal cell surfaces resulting in a reduced number of binding sites for the radiotracer. Our finding is of special interest in the light of a recent study conducted by Raju and colleagues describing autoimmunity in SPS patients against the GABA-A-receptor-associated protein (GABARAP), which is responsible for the stability and surface expression of the GABA-A receptor [14]. The authors concluded that GABARAP acts as an autoantigen in SPS patients in which antibody-mediated blocking results in a decreased availability of central postsynaptic benzodiazepine receptors.…”
Section: Discussionmentioning
confidence: 65%